2004
DOI: 10.1038/sj.npp.1300496
|View full text |Cite
|
Sign up to set email alerts
|

The Psychotomimetic Effects of Intravenous Delta-9-Tetrahydrocannabinol in Healthy Individuals: Implications for Psychosis

Abstract: Recent advances in the understanding of brain cannabinoid receptor function have renewed interest in the association between cannabinoid compounds and psychosis. In a 3-day, double-blind, randomized, and counterbalanced study, the behavioral, cognitive, and endocrine effects of 0, 2.5, and 5 mg intravenous delta-9-tetrahydrocannabinol (D-9-THC) were characterized in 22 healthy individuals, who had been exposed to cannabis but had never been diagnosed with a cannabis abuse disorder. Prospective safety data at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
695
3
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 903 publications
(754 citation statements)
references
References 132 publications
43
695
3
13
Order By: Relevance
“…The inhibition of synaptic transmission in the human cortex by cannabinoids shown in this study probably has a role in the impairment of perception and cognitive function occurring acutely after inhalation of cannabinoids (D'Souza et al, 2004;Ramaekers et al, 2006; for review, see Murray et al (2007)). We also demonstrated that the CB 1 receptor antagonist rimonabant disrupts DSI in the human cortex, a form of short-term synaptic plasticity.…”
Section: Discussionmentioning
confidence: 65%
“…The inhibition of synaptic transmission in the human cortex by cannabinoids shown in this study probably has a role in the impairment of perception and cognitive function occurring acutely after inhalation of cannabinoids (D'Souza et al, 2004;Ramaekers et al, 2006; for review, see Murray et al (2007)). We also demonstrated that the CB 1 receptor antagonist rimonabant disrupts DSI in the human cortex, a form of short-term synaptic plasticity.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have identified environmental risk factors for schizophrenia, like urban place of birth (Pedersen and Mortensen, 2001) and neighborhood environment (van Os et al, 2000), which support the link between a stressful environment and the development of psychosis. Furthermore, cannabis abuse has been identified as a risk factor for schizophrenia (Arseneault et al, 2004), and activation of the hormonal stress response by cannabis could also participate to this phenomenon (D'Souza et al, 2004;D'Souza et al, 2005). Indeed, this sample may be at a higher risk of presenting all these environmental risk factors: for example, approximately 50% of these patients were currently using or abusing cannabis at the time of the study (unpublished data).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, perceptual anomalies are incorporated within a cognitive model of paranoid delusions, where paranoid beliefs arise from an attempt to explain anomalous and odd internal experiences (Freeman et al, 2002). Indeed, research has shown that perceptual anomalies increase the risk for the development of delusional ideas (Krabbendam et al, 2004) and anomalies of experience caused by illegal drug use have also been linked to delusional ideation (D'Souza et al, 2004). Our mediation model suggests that one route that people with sleep problems may experience paranoia is via perceptual anomalies.…”
Section: Perceptual Anomalies and Paranoiamentioning
confidence: 99%